Assessing the Performance of Value-at-Risk Models in Chinese Stock Market - Lin, Lin (2008)
In this paper, parametric, nonparametric, and semi-parametric models are applied to a hypothetical portfolio - Shanghai Stock Exchange Composite Index to estimate Value-at-Risk in Chinese market. In order to assess the performance of different approaches, the statistic features such as kurtosis, skewness and autocorrelation of daily return have been studied. In addition, this article analyzes the advantages and disadvantages of each model and implements back-tests to check the validation of them. The main finding of this article is that Filtered Historical Simulation proves to be the most appropriate approach to estimate Value-at-Risk in Chinese financial market.